PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PERSPEKTIF ISLAM (Studi pada Program Kemitraan Bina Lingkungan PT Kertas Leces) - Trisnawati, Trisnawati (IQTISHODUNA, 2016)
Corporate Social Responsibility (CSR) or corporate social responsibility undertaken by PT KertasLeces known as CSR (Community Development Partnership Program). This study used descriptive qualitativemethod, which the researchers suggested empirical problem at PT Kertas Leces beforehand which thenbecame the basis of the holding of a study with a focus on the implementation of Corporate Social Responsibility(CSR) or Community Development Partnership Program (CSR) in the perspective of Islam. Based on thesurvey results revealed that the outputs or outcomes of its Corporate Social Responsibility (CSR) or CommunityDevelopment Partnership Program (CSR) PT Kertas Leces are their environmental management work thenfulfilled the rights of employees and their families, Small and Medium Enterprises (SMEs) or partner inmateswho received soft loan can be independent and grow, their waste handling is good then created the environmentaround PT Kertas Leces, and their social investments PT Kertas Leces to the people around. In the Islamicperspective of what is done by PT Kertas Leces is appropriate, namely in terms of the values of (a) preservationof the environment and preserve it; (B) efforts to eradicate poverty; (C) putting something morally cleanerthan morally dirty, although bringing greater profits; and (d) to be honest and trustworthy.